(untitled) (Cambridge,New York, 2001)
This collection takes stock of 'the state of the welfare state': How can we build a theory of the welfare state? How did the post-World War II welfare state relate to economic development? How do welfare states change? How did the reforms of pension systems--a key welfare state sector--develop in OECD countries? How did the most developed 'Nordic welfare state' fare? How viable are today's advanced welfare states in the international economy? How may we recast the European welfare states for the twenty-first century?
Keywords: Welfare state futures,Chính sách phúc lợi xã hội